Manifestation Of Criminal Sanctions In The Judicial Process On Criminal Actor Of Negligence (Culpa) - Ahmad Ghifar Al Ahfaqsyi; Siti Rodhiyah Dwi Istinah (Law Development Journal, 2020)
The purpose of this research is to study and analyze manifestation of criminal sanctions in the process of prosecuting the perpetrator of a criminal offense due to negligence (Culpa). In this study the authors used sociological juridical methods with descriptive research specifications. The data sources used are primary and secondary data. Based on the results of the research, the conclusion is that in case No.207 / Pid.Sus / 2019 / PNClcp, it is in accordance with the provisions of both formal criminal law and material criminal law and the conditions that can be convicted of a defendant, this is based on trial examination, where the evidence submitted by the public prosecutor, including the testimony of the witnesses which are compatible with the statement of the defendant who honestly admitted to the act he had committed, the Panel of Judges at the Cilacap District Court in the case stated that the elements of the defendant's actions matched the formulation of the offense contained in Article 310 paragraph (4) of Act No. 22 of 2009 on Traffic and Road Transportation.